2015
DOI: 10.1063/1.4917191
|View full text |Cite
|
Sign up to set email alerts
|

Towards an on-chip platform for the controlled application of forces via magnetic particles: A novel device for mechanobiology

Abstract: Magnetic cell manipulation utilizing magnetic particles and diamagnetic collagen fibers J. Appl. Phys. 99, 08R906 (2006); 10.1063/1.2175957Superconducting quantum interference device-based magnetic nanoparticle relaxation measurement as a novel tool for the binding specific detection of biological binding reactions (abstract)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recently, magnetic tweezers and micromagnetophoretic patterns offer significant advancements by overcoming the abovementioned complications toward precise particle, droplet, and cell manipulations. Furthermore, we have demonstrated a class of integrated circuits of micromagnetophoretic patterns, such as conductors, diodes, capacitors, and transistors to execute sequential and parallel operations on an ensemble of single particles and cells .…”
Section: Multifarious Transit Gating Of Particles Moving Along the Rementioning
confidence: 99%
“…Recently, magnetic tweezers and micromagnetophoretic patterns offer significant advancements by overcoming the abovementioned complications toward precise particle, droplet, and cell manipulations. Furthermore, we have demonstrated a class of integrated circuits of micromagnetophoretic patterns, such as conductors, diodes, capacitors, and transistors to execute sequential and parallel operations on an ensemble of single particles and cells .…”
Section: Multifarious Transit Gating Of Particles Moving Along the Rementioning
confidence: 99%
“…The viscous friction on particles in a fluid is described by the Stokes equation (see Supplementary Information for details). For a typical manipulation velocity v= 10 µm/s, it is equal to 85 fN and can be neglected if compared to F m , which is in the order of hundreds pN 41,49 . Even gravity and buoyancy forces are much less intense (≈ 10 fN) than F m .…”
Section: Simulations Of Magnetic Forces Exerted On Cellsmentioning
confidence: 99%
“…Crucial for applications, in ref. 49 some of the authors demonstrated that the magnetic force can be tuned varying the intensity of H e, which affects the beads magnetization and consequently F m (see the first term in Equation 1). Our platform thus provides an efficient method for applying localized and tuneable magnetic forces to the cell, whose intensity can be quantitatively evaluated and correlated to the observation of confocal microscopy.…”
Section: Simulations Of Magnetic Forces Exerted On Cellsmentioning
confidence: 99%
“…The individual particle manipulation, on the contrary, allows 1D, 2D, and 3D positioning, as well as possible orientation control of an individual magnetic microparticle. 1D transportation has been carried out by serpentine microcurrent lines or by zig‐zag micropatterned domain walls . Electromagnetic needles have also been used for 1D magnetophoretic attraction and 2D guiding of superparamagnetic microparticles, as well as DNA stretching.…”
Section: Introductionmentioning
confidence: 99%
“…Other, 2D transportation with potential rotation of microparticles has been achieved by micropatterned thin film magnetic elements and current wires, two‐pair electromagnets, as well as magnetooptical tweezers . The systems using micropatterned elements are usually coupled with an external magnetic field coming from a permanent magnet, single, or two pair Helmholtz coils or electromagnets . In addition, multipole solenoids enable 3D positioning…”
Section: Introductionmentioning
confidence: 99%